ROLE OF THE PEDAGOGICAL SKILLS IN TEACHING FOREIGN LANGUAGES (Journal of Universal Science Research, 2023)
While the world is expanding in all fields, learning foreign languages is becoming an increasingly important part of education. Thus, many instructors are seeking to enhance their pedagogical skills by collaborating with overseas experts and adapting state-of-the-art, interactive teaching methods into the curriculum to more successfully distribute content and cooperate with their colleagues and students. This article is devoted to raising one of today`s trending topics, namely teachers` role in acquiring languages far more efficiently and indicating factors in the development of pedagogical performance in the classroom.